Multidisciplinary functions of blockchain technology in AI and IoT applications - Chowdhury, Niaz; Deka, Ganesh Chandra 1969- (A volume in the Advances in data mining and database management (ADMDM) book series, 2021)
"This edited book deliberates upon prospects of blockchain technology for facilitating the analysis and acquisition of big data using AI and IoT devices in various application domains" - Provided by publisher